Message from the Workshop Organizers - ADMNET 2014 (2014 IEEE 38th International Computer Software and Applications Conference Workshops, 2014)
Presents the introductory welcome message from the conference proceedings. May include the conference officers' congratulations to all involved with the conference event and publication of the proceedings record.